Structural Elucidation and Antibacterial Evaluation of Natural Products from the Nigric Section of Aspergillus Species against Sorbitol-Positive and -Negative Escherichia coli - Iheukwumere, I. H.; Iheukwumere, C. M.; Obianom, A. O.; Nnadozie, C. H.; Onwuasoanya, U. F.; Oduoye, O. T.; Ike, V. E.; Obiefuna, O. H.; Igboanugo, E. U.; Ejike, C. E.; Udeagbara, O. E.; Ochibulu, S. C.; et al. (IPS Journal of Natural Products, 2025)
Studies have shown that limited availability, supply shortages and pricing of conventional antibiotics including carcinogenic and mutagenic nature are serious global problems that restrict access to effective treatment for common bacterial infections, and this may not only worsen clinical outcomes but potentially accelerate the development of antibiotic resistance. Hence this study focused on the structural elucidation of antibacterial substances from Mycelia of Negric section of Aspergillus species using natural sources. The fungal isolates were isolated from garden soil samples using standard microbiological techniques. The fungi were grown in a submerged medium prepared from Phoenix dactylifera (PD) fruits (20g), Chrysophyllum albidum (C.A) fruits (10g), Glycine max (GM) peel (10g) and Musa paradisiaca (MP) peel (10g). The antibacterial substances were precipitated, eluted, purified and structurally elucidated using column chromatographic, thin layer chromatographic and C-S-MS techniques respectively. The Aspergillus species isolated were Aspergillus niger strain HUS1 (ANH1), Aspergillus aculeatus strain AN5 (AAA5) and Aspergillus awamori strain DN-SN2 (AAD2). The optical growth and production of antibacterial substances occurred when the pH, Temperature, Carbon Source and nitrogen source were 7.0, 25, and sugar extracted from PD and NOdz respectively. The purified fractions; oleic acid (N1) > 1-docosene (N2) > I-octadecene (N3) > 2,3 furanone-4-hydroxyl (N4) from ANH1 showed significant (P<0.05) inhibitory activities against sorbitol positive and sorbitol negative Escherichia coli; Escherichia coli O157: H7 strain MB4-1 (SECM41) and Escherichia coli HH35 (SECH35). Similarly trans (2-doscenyl) succinic acid (A2) > E-15-hepadecenal (A1) > silane ethyl-trimethoxy (A3) from AAA5 and oleic acid (D1) > hexacosanoic acid (D2) > n-hexadecenoic acid (D3) > 9-octadecenoic acid (Z) methyl ester (D4) from AAD2 also showed significant (P<0.5) pronounced activities against the Sor+ and Sor- Escherichia coli. From this study, the purified fractions from ANH1, AAA5 and AAD2 showed pronounced activities against uropathogenic Escherichia coli and formed the basis of newer antibiotics from natural sources.